Salivary mucoepidermoid carcinoma, auclair vs brandwein grading system: A histopathological comparative study - Ahmed , Omar I; Al-Azzawi , Lehadh M (Journal of Baghdad College of Dentistry, 2020)
Background: The grading systems of salivary mucoepidermoid carcinoma depend on different histologic and morphologic features. The aim of this study was to compare between Auclair and Brandwein systems according to their histologic criteria, and the type of cell predominant. Materials and Methods: Twenty-one case included hematoxylin-eosin (H&E) stained tissue slides that were diagnosed as MEC, originally categorized into low and high grade type regardless of the grading system, have meticulously undergone histopathologic review. The sample was graded according to criteria owing to Auclair and Brandwein methods. The predominant type of cells was determined by microscopic examination according to grade of tumor. Results: Regarding the Auclair method, 10 cases (47.6%) were low grade tumor, 11 cases (52.2%) were high grade type and none of them were intermediate type. By using Brandwein system for the same sample, 4 cases (19%) were low grade, 13 cases (61%) were a high grade tumor, and 4 cases (19%) were intermediate type. Even though, for both systems more than 35% of cases were predominated with epidermoid cells, and <15% showed mucous and intermediate cell predominance for each, whereas >30% were exhibited a mixed type of tumor cells. However, there was a significant correlation between the grading systems applied and the type of cell predominance (p-value <0.05). Conclusion: The number of cases distributed according to Brandwein system was increased as the level of histologic grade being raised, and the type of cells, which are relatively predominant, may be valuable in determining the histologic grade of tumors. Keyword: Mucoepidermoid carcinoma (MEC), Auclair system, Brandwein system.